2021
DOI: 10.3390/membranes11090684
|View full text |Cite
|
Sign up to set email alerts
|

Active Edible Films Fortified with Natural Extracts: Case Study with Fresh-Cut Apple Pieces

Abstract: The main aim of the study was to prepare the edible films based on carrageenan/chitosan and incorporate them into the following matrices: the natural extracts of Clitoria ternatea, Brassica oleracea, and Ipomea batatas. The films were characterized by TPC (total polyphenols content), antioxidant activity, and textural properties. Experimentally produced films were added in the packaging of freshly cut apple pieces, and the apple pieces were dipped into the films produced from carrageenan and chitosan. The appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…The increase in tensile strength was due to the reduced water content in the bioplastic because it had been absorbed by chitosan as an organic polysaccharide. Therefore, the molecular structure of bioplastics becomes denser and more homogeneous, which causes the tensile strength to increase [47,48]. This is also in line with conducted research which states that the addition of chitosan in PLA causes the tensile strength to increase based on research that has been carried out by [49] regarding the effect of the homogenization method and the content of carvacrol on the microstructure and physical properties of chitosan-based films.…”
Section: Effect Of Variations In Pla-chitosan-teo Concentration On Mechanical Characteristics Of Food Packagingsupporting
confidence: 72%
“…The increase in tensile strength was due to the reduced water content in the bioplastic because it had been absorbed by chitosan as an organic polysaccharide. Therefore, the molecular structure of bioplastics becomes denser and more homogeneous, which causes the tensile strength to increase [47,48]. This is also in line with conducted research which states that the addition of chitosan in PLA causes the tensile strength to increase based on research that has been carried out by [49] regarding the effect of the homogenization method and the content of carvacrol on the microstructure and physical properties of chitosan-based films.…”
Section: Effect Of Variations In Pla-chitosan-teo Concentration On Mechanical Characteristics Of Food Packagingsupporting
confidence: 72%
“…Moreover, EC can be functionalized with antimicrobials, antioxidants, or nutraceuticals. Plant essential oils (EO) are widely used for their antioxidant effect and/or large spectrum of action against microorganisms, for example, oregano or clove EOs incorporated into whey protein isolate edible films as natural antimicrobials aimed to enhance the microbial quality of poultry [ 12 ]; quince seed mucilage film with oregano or thyme EO extended the shelf life of rainbow trout fillets by 3–11 days during refrigerated storage [ 13 ]; carrageenan/chitosan edible films functionalized with natural extracts of Clitoria ternatea, Brassica oleracea, and Ipomea batatas applied to fresh-cut apple pieces [ 14 ]; bi-layer of whey protein and xanthan gum with clove applied on tomatoes [ 15 ]. Coatings applied on fresh-cut vegetables and fruits, for example, whey proteins and zein thin layer applied on peeled garlic clove [ 16 ]; whey protein/pectin edible coating applied on fresh fruit and vegetable [ 17 ] were also effective in prolonging shelf-life.…”
Section: Introductionmentioning
confidence: 99%
“…Moghadam et al [ 3 ] reported that active film based on protein-rich mung bean flour incorporating pomegranate peel exhibited good antioxidant and antimicrobial properties. Janikova et al [ 21 ] observed that addition of natural extracts, particularly from Clitoria ternatea , Brassica oleracea , and Ipomea batatas , in the protein-polysaccharide based edible film emulsion and treatment with fresh cut apples was highly effective in controlling the surface browning and significantly extended their shelf life. To the best of our knowledge, no prior study is available on the fabrication of mung bean flour-based edible film emulsion with clove essential oil and homogenization using sonication to develop biodegradable edible films with strong physical, biochemical, and functional properties.…”
Section: Introductionmentioning
confidence: 99%